2021
DOI: 10.1002/nau.24644
|View full text |Cite
|
Sign up to set email alerts
|

High percentage of neurologic deficits in the electrophysiology study of the lower urinary tract in patients with detrusor underactivity and chronic urinary retention

Abstract: Objectives: Both detrusor underactivity (DU) and bladder outlet obstruction are the common causes of chronic urinary retention. Some novel treatment approaches focus on modulating micturition reflex and external urethral sphincter (EUS) function. This study used electrophysiologic (EP) studies to investigate the micturition reflex and EUS conditions of chronic urinary retention patients. Methods: Sixty patients with urodynamic DU and chronic urinary retention were studied using (1) bulbocavernous reflex (BCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some patients with clinical DU might be due to absent or diminished bladder sensation, resulting in inability to initiation or early termination of the completeness of voiding process 12 . From the electromyographic study of patients with DU and chronic urinary retention, we found the causes of DU included bladder dysfunction, neuropathy in sacral reflexes, pudendal nerve, and urethral sphincter innervation 24 . Bladder sensation was decreased and CBC was larger in the DU group than in the detrusor hyperactivity and inadequate contractility, hypersensitive bladder, and DO groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with clinical DU might be due to absent or diminished bladder sensation, resulting in inability to initiation or early termination of the completeness of voiding process 12 . From the electromyographic study of patients with DU and chronic urinary retention, we found the causes of DU included bladder dysfunction, neuropathy in sacral reflexes, pudendal nerve, and urethral sphincter innervation 24 . Bladder sensation was decreased and CBC was larger in the DU group than in the detrusor hyperactivity and inadequate contractility, hypersensitive bladder, and DO groups.…”
Section: Discussionmentioning
confidence: 99%
“…The study also included patients with closed bladder neck while voiding. If the impact from BOO results in afferent or efferent neuropathy, surgery may be not satisfactory [ 30 ].…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%